The effects of creatine and glycerol hyperhydration on running economy in well trained endurance runners - Beis, L. Y.; Polyviou, T.; Malkova, D.; Pitsiladis, Y. P. (Journal of the International Society of Sports Nutrition, 2011)
Ingestion of creatine (Cr) and glycerol (Gly) has been reported to be an effective method in expanding water compartments within the human body, attenuating the rise in heart rate (HR) and core temperature (Tcore) during exercise in the heat. Despite these positive effects, a substantial water retention could potentially impair endurance performance through increasing body mass (BM) and consequently impacting negatively on running economy (RE). The objective of the present study was to investigate the effects of a combined Cr and Gly supplementation on thermoregulatory and cardiovascular responses and RE during running for 30 min at speed corresponding to 60% of maximal oxygen uptake (VO2max) in hot and cool conditions. Methods: Cr * H2O (11.4 g), Gly (1 g * kg-1 BM) and Glucose polymer (75 g) were administered twice daily to 15 male endurance runners during a 7-day period. Exercise trials were conducted pre- and post-supplementation at 10 and 35 degreesC and 70% relative humidity. Results: BM and total body water increased by 0.90 +/- 0.40 kg (P < 0.01; mean +/- SD) and 0.71 +/- 0.42 L (P < 0.01), respectively following supplementation. Despite the significant increase in BM, supplementation had no effect on VO2 and therefore RE. Both HR and Tcore were attenuated significantly after supplementation (P < 0.05, for both). Nevertheless, thermal comfort and rating of perceived exertion was not significantly different between pre- and post-supplementation. Similarly, no significant differences were found in sweat loss, serum osmolality, blood lactate and in plasma volume changes between pre- and post-supplementation. Conclusions: Combining Cr and Gly is effective in reducing thermal and cardiovascular strain during exercise in the heat without negatively impacting on RE.